2017
DOI: 10.3389/fmicb.2017.00588
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics and Transcriptional Analysis of Flavobacterium columnare Strain ATCC 49512

Abstract: Flavobacterium columnare is a Gram-negative fish pathogen causing columnaris disease in wild and cultured fish species. Although the pathogen is widespread in aquatic environments and fish worldwide, little is known about biology of F. columnare and mechanisms of columnaris disease pathogenesis. Previously we presented the complete genome sequence of F. columnare strain ATCC 49512. Here we present a comparison of the strain ATCC 49512 genome to four other Flavobacterium genomes. In this analysis, we identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 108 publications
(140 reference statements)
3
27
0
Order By: Relevance
“…Further, recent comparative analyses identified all of the T9SS genes in the genomes of each of nine F. columnare strains examined (41,42). For all members of the phylum Bacteroidetes that have the T9SS genes, gldK, gldL, gldM, and gldN are invariably located together in this order as an operon (20,21).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, recent comparative analyses identified all of the T9SS genes in the genomes of each of nine F. columnare strains examined (41,42). For all members of the phylum Bacteroidetes that have the T9SS genes, gldK, gldL, gldM, and gldN are invariably located together in this order as an operon (20,21).…”
Section: Figmentioning
confidence: 99%
“…The action of the gliding motor on SprB proteins that are attached to the substratum results in gliding motility. F. columnare has an SprB ortholog that is thought to be involved in gliding (42). Not surprisingly, deletion of the core F. columnare T9SS gene gldN resulted not only in secretion defects but also in a loss of motility.…”
Section: Fig 10mentioning
confidence: 99%
“…The 6-phosphofructokinase 1 (Pf1_00390) and pyruvate kinase (Pf1_01219) are two important enzymes which can regulate the rate of reaction in glycolysis. Moreover, compared genomic analysis showed that some carbohydrate metabolism components and pathways are unique, such as starch and sucrose utilization pathways are present only in F. johnsoniae and F. branchiophilum [16]. Diversity pathways of amino acids biosynthesis and metabolism reflect a highly selfsufficient and unique style in utilizing nutrients.…”
Section: Phylogenetic Analysis and Genotypingmentioning
confidence: 99%
“…Totally 70 genes in nitrogen metabolism pathways were presented, including glycine, serine and threonine metabolism, phenylalanine, tyrosine and tryptophan biosynthesis, valine, leucine and isoleucine degradation, alanine, aspartate and glutamate metabolism, arginine and proline metabolism, and histidine metabolism. Genome analysis of F. columnare ATCC 49512 indicated it is capable of denitrification, which would enable anaerobic growth in aquatic pond sediments [16]. After the amino acid degradation, all the nitrogen was excreted in the form of putrescine and NH 3 .…”
Section: Phylogenetic Analysis and Genotypingmentioning
confidence: 99%
See 1 more Smart Citation